Phenotypes of GNAO1 Variants in a Chinese Cohort - Yang, Xiaoling; Niu, Xueyang; Yang, Ying; Cheng, Miaomiao; Zhang, Jing; Chen, Jiaoyang; Yang, Zhixian; Zhang, Yuehua (Frontiers in Neurology, 2021)
This study aimed to analyze the genotypes and phenotypes of GNAO1 variants in a Chinese cohort. Seven male and four female patients with GNAO1 variants were enrolled, including siblings of brothers. Ten different GNAO1 variants (nine missense and one splicing site) were identified, among which six were novel. All the variants were confirmed to be de novo in peripheral blood DNA. Eight (73%, 8/11) patients had epilepsy; the seizure onset age ranged from 6 h after birth to 4 months (median age, 2.5 months). Focal seizures were observed in all eight patients, epileptic spasms occurred in six (75%, 6/8), tonic spasm in four (50%, 4/8), tonic seizures in two, atypical absence in one, and generalized tonic–clonic seizures in one. Seven patients had multiple seizure types. Eight (73%, 8/11) patients had movement disorders, seven of them having only dystonia, and one having dystonia with choreoathetosis. Varying degrees of developmental delay (DD) were present in all 11 patients. The phenotypes were diagnosed as early infantile epileptic encephalopathy (EIEE) in two (18%) patients, which were further diagnosed as West syndrome. Movement disorders (MD) with developmental delay were diagnosed in two (18%) brothers. EIEE and MD were overlapped in six (55%) patients, among which two were diagnosed with West syndrome, one with Ohtahara syndrome, and the other three with non-specific EIEE. One (9%) patient was diagnosed as DD alone. The onset age of GNAO1-related disorders was early infancy. The phenotypic spectrum of GNAO1 included EIEE, MD with DD, and DD alone.